Electromagnetic shielding film and preparation method thereof

By combining polyacrylate emulsion and high magnetic permeability soft magnetic powder, an electromagnetic shielding film with high magnetic permeability was prepared, which solved the problem of insufficient aging performance of electromagnetic shielding materials in the prior art under high temperature and high humidity environment. It achieves efficient electromagnetic shielding effect and cost reduction.

CN114245699BActive Publication Date: 2024-12-20SUZHOU FINESET MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111535435.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-15
Publication Date
2024-12-20
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

The aging performance of existing electromagnetic shielding materials in high temperature and high humidity environments is insufficient, especially the high price and easy hydrolysis of polyurethane-type aqueous glue, which leads to a decrease in magnetic permeability and is difficult to meet the demand for electronic devices to resist electromagnetic interference.

Method used

Using a combination of a polyacrylate emulsion and a soft magnetic powder with a magnetic permeability of 150H/m, a solid-to-solid mass ratio of 1:9 was combined with diluents, ammonia, thickeners, defoamers and wetting agents, through Emulsion polymerization synthesizes an inorganic solvent-friendly electromagnetic shielding film, and uses the low glass transition temperature and excellent phase angle characteristics of the polyacrylate emulsion to prepare an electromagnetic shielding film with high magnetic permeability.

Benefits of technology

The magnetic permeability at 3MHz frequency is achieved to reach more than 105H/m, which improves the performance of the electromagnetic shielding film, reduces production costs, and maintains stable performance in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003413056720000071
    Figure BDA0003413056720000071
Patent Text Reader

Abstract

The present invention discloses an electromagnetic shielding film and a preparation method thereof, wherein the raw materials of the electromagnetic shielding film include polyacrylate emulsion, diluent, ammonia water, thickener, defoamer, wetting agent and soft magnetic powder, wherein the polyacrylate emulsion and the soft magnetic powder are added according to a solid-to-solid mass ratio of 1:9, the glass transition temperature of the polyacrylate emulsion is not higher than ‑15°C, and the phase angle at 120°C and 0.1Hz is less than 15°. The electromagnetic shielding film using the formula of the present invention has a magnetic permeability of more than 105H / m at a frequency of 3 MHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electromagnetic shielding material, in particular to an electromagnetic shielding film and a preparation method thereof. Background Art

[0002] In electronic devices, the circuit itself has low voltage and low power consumption, which significantly reduces the ability of the circuit to resist electromagnetic interference (EMI). Plating anti-EMI materials on the product shell can not only protect the product from external EMI, but also reduce its own interference to the outside world. The EU 89 / 336 / EEC (EMC) standard has clearly stated that electronic products must be plated or covered with anti-EMI materials on the inner wall of the product shell.

[0003] An important EMI material on the market is EMI film. In this material, the electronic shielding effect is played by soft magnetic powder, such as sendust powder, etc. In addition, a medium is needed to adhere the soft magnetic powder into a film, which is generally a binder.

[0004] The adhesive for bonding soft magnetic powder can be divided into two types according to the solvent: solvent-based adhesive and water-based adhesive. Water-based adhesive is favored by EMI film manufacturers due to its low odor and environmental friendliness. At present, most of the water-based adhesives for EMI bonding on the market are polyurethane-based, which are relatively expensive. At the same time, since polyurethane is easily hydrolyzed, the corresponding EMI film has problems with aging performance in high temperature and high humidity environments. In contrast, polyacrylate emulsions are low in price and have extremely excellent aging performance, but such products are rarely seen on the market. Summary of the invention

[0005] The object of the present invention is to overcome the deficiencies of the prior art and provide an electromagnetic shielding film with better magnetic permeability.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an electromagnetic shielding film, the raw materials of the electromagnetic shielding film include polyacrylate emulsion, diluent, ammonia water, thickener, defoaming agent, wetting agent and soft magnetic powder, wherein the polyacrylate emulsion and soft magnetic powder are added according to a solid-to-solid mass ratio of 1:9, the glass transition temperature of the polyacrylate emulsion is not higher than -15°C, and the phase angle at 120°C and 0.1Hz is less than 15°.

[0007] The soft magnetic powder used here has a magnetic permeability of 150 H / m.

[0008] Here, the solid-to-solid mass ratio of the polyacrylate emulsion and the soft magnetic powder is such that if the amount of soft magnetic powder added is small, the magnetic permeability decreases, and if the amount added is increased, the powder is easy to fall off, so the solid-to-solid mass ratio between the two is selected to be 1:9.

[0009] As a specific implementation, the polyacrylate emulsion comprises the following raw materials by weight: 75-105 parts of hard monomer, 140-170 parts of soft monomer, 7.5-12.5 parts of functional monomer, 0.5-1 part of ammonium persulfate, 220-250 parts of deionized water, and 10-15 parts of emulsifier.

[0010] As a specific implementation, the hard monomer in the raw materials of the polyacrylate emulsion is selected from at least one of methyl methacrylate, styrene, vinyl acetate, methyl methacrylate, and isobornyl acrylate; the soft monomer is selected from at least one of isooctyl acrylate, ethyl acrylate, or butyl acrylate; and the functional monomer is acrylic acid or a mixture of acrylic acid and 1,6-hexanediol diacrylate.

[0011] As a specific implementation, the emulsifier in the raw material of the polyacrylate emulsion is sodium dodecylbenzene sulfonate.

[0012] As a specific implementation, the preparation process of the polyacrylate emulsion is as follows:

[0013] S1) Preparation of pre-emulsion:

[0014] Weigh the raw materials required for preparing the polyacrylate emulsion, add 60-70% of deionized water and 85-90% of the emulsifier in the raw materials into a 1000 mL three-necked flask at room temperature, stir evenly, then add 90% of the hard monomer, 90% of the soft monomer and 90% of the functional monomer under vigorous stirring to obtain a pre-emulsion;

[0015] S2) Preparation of emulsion

[0016] Add the remaining deionized water and emulsifier to a 1000 mL three-necked flask and stir evenly. Then add the remaining hard monomer, soft monomer and functional monomer under vigorous stirring. Raise the temperature to 80±2° C., add 40% ammonium persulfate, and dissolve the remaining ammonium persulfate in water at a mass ratio of 24:1000. After half an hour, start dripping the above-mentioned aqueous solution of ammonium persulfate and the pre-emulsion obtained in step S1) at 80±2° C., control the dripping time to be 150±1 min, and then continue stirring and reacting at 80±2° C. for 1 hour to obtain the polyacrylate emulsion.

[0017] Here, the polyacrylate emulsion is synthesized via free radical emulsion polymerization, does not contain organic solvents, and is environmentally friendly.

[0018] As a specific implementation manner, the diluent is obtained by mixing water and ethanol in a mass ratio of 1:1.

[0019] As a specific implementation, the glass transition temperature of the polyacrylate emulsion is less than -20°C, and the phase angle at 120°C and 0.1 Hz is less than 10°.

[0020] As a specific implementation manner, the raw materials of the electromagnetic shielding film include, by weight, 5-10 parts of polyacrylate emulsion, 30-40 parts of diluent, 0.2-0.5 parts of ammonia water, 0.5-1.5 parts of thickener, 0.01-0.1 parts of defoaming agent, 0.05-0.2 parts of wetting agent and 22.5-45 parts of soft magnetic powder, wherein the polyacrylate emulsion and the soft magnetic powder are added in a solid to solid mass ratio of 1:9.

[0021] Another object of the present invention is to provide a method for preparing the above electromagnetic shielding film, comprising the following steps:

[0022] The polyacrylate emulsion is diluted with a diluent, and then ammonia water, thickener, defoamer, wetting agent and soft magnetic powder are added and dispersed evenly to obtain a mixed solution. The mixed solution is then coated on a release film with a comma roller and dried to obtain a 100 μm thick dry film. The film is then pressed in a press at 160°C and 18.5 MPa for 5-6 minutes to obtain the required electromagnetic shielding film.

[0023] Due to the application of the above-mentioned technical scheme, the present invention has the following advantages compared with the prior art: the electromagnetic shielding film of the present invention adopts polyacrylate emulsion and soft magnetic powder as its raw materials, the glass transition temperature of the polyacrylate emulsion here is not higher than -15°C, and the phase angle at 120°C and 0.1Hz is less than 15°. The electromagnetic shielding film obtained by combining it with soft magnetic powder with a magnetic permeability of 150H / m has a magnetic permeability of more than 105H / m at a frequency of 3MHz. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0025] Example 1

[0026] 1) Preparation of polyacrylate emulsion A

[0027] Preparation of pre-emulsion A:

[0028] Deionized water (145.7 g) and emulsifier DS-4 (10.87 g) were added to a 1000 mL three-necked flask and stirred evenly. Then, isooctyl acrylate (126 g), methyl methacrylate (92.25 g), acrylic acid (6.75 g) and 1,6-hexanediol diacrylate (2.25 g) were added under vigorous stirring to obtain pre-emulsion A.

[0029] Preparation of Emulsion A:

[0030] Deionized water (75 g) and emulsifier DS-4 (1.63 g) were added to a 1000 mL three-necked flask and stirred evenly. Then, isooctyl acrylate (14 g), methyl methacrylate (10.25 g), acrylic acid (0.75 g) and 1,6-hexanediol diacrylate (0.25 g) were added under vigorous stirring. The temperature was raised to 80° C., ammonium persulfate (0.2 g) was added, 0.3 g of ammonium persulfate was dissolved in 12.5 g of water, and the aqueous solution of ammonium persulfate and pre-emulsion A were added dropwise at 80° C. after half an hour, and the dripping was controlled to be completed within 150 minutes. Then, stirring and reacting were continued at 80° C. for 1 hour to obtain emulsion A with a solid content of 50%.

[0031] 2) Preparation of EMI film A:

[0032] Emulsion A (8 g) was diluted with water (16 g) and ethanol (16 g), and aqueous ammonia (0.36 g), thickener ASE-60 (1 g), defoamer DF-150 (0.04 g), wetting agent PSA336 (0.08 g) and soft magnetic powder XCA-150 (36 g) were added and dispersed evenly to obtain a mixed solution.

[0033] Thickener ASE-60 was purchased from Rohm and Haas Company, USA, and defoamer DF-150 was purchased from Shanghai Sangjing Chemical Co., Ltd.

[0034] The mixed solution was coated on a release film using a comma roller and dried to obtain a dry film with a thickness of 100 μm. The film was then pressed in a press at 160° C. and 18.5 MPa for 6 minutes to obtain EMI film A.

[0035] Example 2

[0036] 1) Preparation of polyacrylate emulsion B

[0037] Preparation of pre-emulsion B:

[0038] Deionized water (145.7 g) and emulsifier DS-4 (10.87 g) were added to a 1000 mL three-necked flask and stirred evenly. Then, isooctyl acrylate (150.75 g), methyl methacrylate (67.50 g), acrylic acid (6.75 g) and 1,6-hexanediol diacrylate (2.25 g) were added under vigorous stirring to obtain pre-emulsion B;

[0039] Preparation of Emulsion B:

[0040] Deionized water (75 g) and emulsifier DS-4 (1.63 g) were added to a 1000 mL three-necked flask and stirred evenly. Isooctyl acrylate (16.75 g), methyl methacrylate (7.5 g), acrylic acid (0.75 g) and hexanediol diacrylate (0.25 g) were then added under vigorous stirring. The temperature was raised to 80° C., ammonium persulfate (0.2 g) was added, 0.3 g of ammonium persulfate was dissolved in 12.5 g of water, and the aqueous solution of ammonium persulfate and pre-emulsion B were added dropwise at 80° C. after half an hour, and the dripping was completed within 150 minutes. The reaction was then continued at 80° C. with stirring for 1 hour to obtain emulsion B with a solid content of 50%.

[0041] 2) Preparation of EMI film B:

[0042] Emulsion B (8 g) was diluted with water (16 g) and ethanol (16 g), and aqueous ammonia (0.36 g), thickener ASE-60 (1 g), defoamer DF-150 (0.04 g), wetting agent PSA336 (0.08 g) and soft magnetic powder XCA-150 (36 g) were added and dispersed evenly to obtain a mixed solution.

[0043] The mixed solution was coated on a release film using a comma roller and dried to obtain a dry film with a thickness of 100 μm. The film was then pressed in a press at 160° C. and 18.5 MPa for 6 minutes to obtain EMI film B.

[0044] Example 3

[0045] 1) Preparation of polyacrylate emulsion C

[0046] Preparation of pre-emulsion C:

[0047] The preparation method of pre-emulsion A is the same as that of pre-emulsion A except that the amount of 1,6-hexanediol diacrylate added is adjusted to 4.5 g.

[0048] Emulsion C preparation:

[0049] The preparation method of emulsion A is the same as that of emulsion C except that pre-emulsion C is used and the amount of 1,6-hexanediol diacrylate added is adjusted to 0.5 g.

[0050] 2) Preparation of EMI film C:

[0051] The preparation method was the same as EMI membrane A except that emulsion C was used.

[0052] Example 4

[0053] 1) Preparation of polyacrylate emulsion D

[0054] Preparation of pre-emulsion D:

[0055] The preparation method of pre-emulsion B is the same as that of pre-emulsion B except that the amount of 1,6-hexanediol diacrylate is adjusted to 4.5 g.

[0056] Emulsion D preparation:

[0057] The preparation method of emulsion B is the same as that of emulsion D except that pre-emulsion D is used and the amount of 1,6-hexanediol diacrylate added is adjusted to 0.5 g.

[0058] 2) Preparation of EMI film D:

[0059] The preparation method was the same as EMI membrane B except that Emulsion D was used.

[0060] Example 5

[0061] 1) Preparation of polyacrylate emulsion E

[0062] Preparation of pre-emulsion E:

[0063] The preparation method is the same as that of pre-emulsion B except that 1,6-hexanediol diacrylate is not added.

[0064] Preparation of Emulsion E:

[0065] The preparation method is the same as that of pre-emulsion B, except that pre-emulsion E is used and 1,6-hexanediol diacrylate is not added.

[0066] EMI film E preparation:

[0067] The preparation method was the same as EMI membrane B except that Emulsion E was used.

[0068] Comparative Example 1

[0069] Preparation of pre-emulsion F:

[0070] Deionized water (145.7 g) and emulsifier DS-4 (10.87 g) were added to a 1000 mL three-necked flask and stirred evenly. Then, isooctyl acrylate (83.25 g), methyl methacrylate (135 g), acrylic acid (6.75 g) and hexanediol diacrylate (2.25 g) were added under vigorous stirring to obtain pre-emulsion F.

[0071] Emulsion F preparation:

[0072] Deionized water (75 g) and emulsifier DS-4 (1.63 g) were added to a 1000 mL three-necked flask and stirred evenly. Then, isooctyl acrylate (9.25 g), methyl methacrylate (15 g), acrylic acid (0.75 g) and hexanediol diacrylate (0.25 g) were added under vigorous stirring. The temperature was raised to 80° C., and ammonium persulfate (0.2 g) was added. Half an hour later, a solution of ammonium persulfate (0.3 g) in water (12.5 g) and pre-emulsion F were added dropwise at 80° C., and the mixture was dripped within 150 minutes. The mixture was then stirred and reacted at 80° C. for 1 hour to obtain emulsion F with a solid content of 50%.

[0073] EMI film F preparation:

[0074] The preparation method is the same as EMI membrane A except that emulsion F is used.

[0075] Comparative Example 2

[0076] Preparation of pre-emulsion G:

[0077] The preparation method of pre-emulsion F is the same as that of pre-emulsion F except that the amount of 1,6-hexanediol diacrylate added is adjusted to 4.5 g.

[0078] Emulsion G preparation:

[0079] The preparation method of emulsion F is the same as that of emulsion F except that pre-emulsion G is used and the amount of 1,6-hexanediol diacrylate added is adjusted to 0.5 g.

[0080] EMI film G preparation:

[0081] The preparation method is the same as EMI membrane A except that emulsion G is used.

[0082] Comparative Example 3

[0083] Preparation of pre-emulsion H:

[0084] The preparation method of pre-emulsion B was the same as that of pre-emulsion B except that isooctyl thioglycolate (0.56 g) was added instead of 1,6-hexanediol diacrylate.

[0085] Emulsion H preparation:

[0086] The preparation method of emulsion B was the same as that of emulsion B except that pre-emulsion H was used and isooctyl thioglycolate (0.063 g) was added instead of hexanediol diacrylate.

[0087] EMI membrane H preparation:

[0088] The preparation method was the same as EMI membrane B except that emulsion H was used.

[0089] The following performance tests were performed on the EMI films obtained in the above Examples 1 to 5 and Comparative Examples 1 to 3. The test results are shown in Table 1:

[0090] (I) Magnetic permeability test: The WK65120B high-precision impedance analyzer produced by Suzhou Yudeng Electronic Technology Co., Ltd. was used to perform the test and record the 3MHz magnetic permeability data.

[0091] (ii) DSC test (glass transition temperature): The test was conducted using the Q-200 instrument from TA Corporation of the United States.

[0092] (III) Rotational rheometer test phase angle: The test was performed using TA's HR-2.

[0093] Table 1

[0094]

[0095] From Table 1, by comparing Examples 1 to 5 with Comparative Examples 1 and 2, it can be found that when the phase angle is lower than 15°, the conductivity of the EMI film obtained from the emulsion with a Tg higher than -15°C is relatively low; by comparing Examples 1 to 5 with Comparative Example 3, it can be found that when Tg is lower than -15°C, the conductivity of the EMI film obtained from the emulsion with a phase angle greater than 15° is also relatively low.

[0096] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An electromagnetic shielding film, It is characterized in that The raw materials of the electromagnetic shielding film include 5-10 parts of polyacrylate emulsion, 30-40 parts of diluent, 0.2-0.5 parts of ammonia water, 0.5-1.5 parts of thickener, 0.01-0.1 parts of defoamer, 0.05-0.2 parts of wetting agent and 22.5-45 parts of soft magnetic powder in parts by weight, wherein the polyacrylate emulsion and the soft magnetic powder are added in a solid-to-solid mass ratio of 1:9, and the polyacrylate emulsion is added in a solid-to-solid mass ratio of 1:

9. The invention relates to a raw material comprising the following components, in parts by weight: 75-105 parts of hard monomer, 140-170 parts of soft monomer, 7.5-12.5 parts of functional monomer, 0.5-1 part of ammonium persulfate, 220-250 parts of deionized water, and 10-15 parts of emulsifier. The polyacrylate emulsion has a glass transition temperature of not higher than -15°C, and a phase angle of less than 15° at 120°C and 0.1 Hz. The soft magnetic powder has a magnetic permeability of 150 H / m.

2. The electromagnetic shielding film according to claim 1, It is characterized in that The hard monomer in the raw materials of the polyacrylate emulsion is selected from at least one of methyl methacrylate, styrene, vinyl acetate, and isobornyl acrylate; the soft monomer is selected from at least one of isooctyl acrylate, ethyl acrylate, or butyl acrylate; and the functional monomer is acrylic acid or a mixture of acrylic acid and 1,6-hexanediol diacrylate.

3. The electromagnetic shielding film according to claim 2, It is characterized in that The emulsifier in the raw material of the polyacrylate emulsion is sodium dodecylbenzene sulfonate.

4. The electromagnetic shielding film according to claim 1, It is characterized in that The preparation process of the polyacrylate emulsion is as follows: S1) Preparation of pre-emulsion: Weigh the raw materials required for preparing the polyacrylate emulsion, add 60-70% of deionized water and 85-90% of the emulsifier in the raw materials into a 1000 mL three-necked flask at room temperature, stir evenly, then add 90% of the hard monomer, 90% of the soft monomer and 90% of the functional monomer under vigorous stirring to obtain a pre-emulsion; S2) Preparation of emulsion Add the remaining deionized water and emulsifier to a 1000 mL three-necked flask and stir evenly. Then, add the remaining hard monomer, soft monomer and functional monomer under vigorous stirring. Raise the temperature to 80±2°C, add 40% ammonium persulfate, and dissolve the remaining ammonium persulfate in water at a mass ratio of 24:1000. After half an hour, begin to drop the above-mentioned aqueous solution of ammonium persulfate and the pre-emulsion obtained in step S1) at 80±2°C, and control the dripping time to be 150±1min. Then continue to stir and react at 80±2°C for 1 hour to obtain the polyacrylate emulsion.

5. The electromagnetic shielding film according to claim 1, It is characterized in that The diluent is obtained by mixing water and ethanol in a mass ratio of 1:

1.

6. The electromagnetic shielding film according to claim 1, It is characterized in that The polyacrylate emulsion has a glass transition temperature of less than -20°C, and a phase angle of less than 10° at 120°C and 0.1 Hz.

7. The method for preparing an electromagnetic shielding film according to any one of claims 1 to 6, It is characterized in that The following steps are involved: The polyacrylate emulsion is diluted with a diluent, and then ammonia water, thickener, defoamer, wetting agent and soft magnetic powder are added and dispersed evenly to obtain a mixed solution. The mixed solution is then coated on a release film with a comma roller and dried to obtain a 100 μm thick dry film. The film is then pressed in a press at 160°C and 18.5 MPa for 5-6 minutes to obtain the required electromagnetic shielding film.

Citation Information

Patent Citations

  • Polyacrylate emulsion pressure-sensitive adhesive for PVC (polyvinyl chloride) cold laminating films and preparation method thereof

    CN106833447A

  • Electromagnetic wave shielding material and preparation method thereof

    CN113727592A